The Effect of Motivation, Discipline, and Work Environment on Teachers’ Performance through Organizational Commitment - Rini Wijayaningsih (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Improving teacher performance remains a major challenge in the education sector, especially when resources are limited. This study aims to analyze the direct and indirect effects of motivation, discipline, and work environment on teacher performance through organizational commitment as a mediating variable. The research used a quantitative approach with a census method involving all teachers in one educational institution. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS software. The results show that motivation, discipline, and work environment have significant positive effects on organizational commitment and teacher performance. Organizational commitment also significantly mediates the relationship between the three independent variables and performance, with partial mediation occurring in each path. The model explains 59.8 percent of the variance in commitment and 67.4 percent of the variance in teacher performance. These findings confirm that efforts to improve teacher performance will be more effective if schools first strengthen teachers’ sense of dedication and loyalty. School leaders are recommended to develop integrated programs that simultaneously enhance motivation, maintain positive discipline, and create a supportive work environment. This approach is expected to produce sustainable improvements in the quality of learning and overall school achievement.